From island mass tourism to rural tourism In Madeira: Is there a place for a re-definition of islands image? - Almeida,António Manuel Martins de (2010)
It is now well acknowledged that the competitive edge of islands´ mature tourist destinations relies on the development of new niche markets such as the rural tourism sector. Further, alternative market segments such as the eco-tourism and the cultural tourism have been targeted by most Destinations Management Organisations on islands. Rural tourism is a very recent but growing market niche in peripheral areas offering mass tourism products. For that reason the aim of this paper is to provide a better understanding of the image of this emerging industry here in Madeira based on a sample of 150 visitors. Multivariate descriptive analysis is applied to ´built-up´ the image of the rural tourism according to socioeconomic, travel-related features, and cognitive and emotional factors as it is usual in the destination image literature. This paper fills a void in the literature concerning the rural tourism sector as the factors attracting tourists to the emerging rural tourism industry in Madeira and policy recommendations put forward.